PERANCANGAN MEDIA PROMOSI BATIK KOTA MOJOKERTO MELALUI AMBIENT SEBAGAI UPAYA MENDUKUNG PROGRAM MOJOKERTO SERVICE CITY - Lestari, Dian Wahyu Tri; Budiardjo, Hardman; Rizky, Muhammad (Jurnal Art Nouveau, 2016)
Abstrak: Mojokerto is one of the towns in East Java province which lies 50 km southwest of Surabaya. Mojokerto is exceptional in the history of Indonesia since the city was formerly the capital of the Majapahit Kingdom, which is one of the largest Hindu-Buddhist kingdoms in Indonesia. Service city concept of Mojokerto must be supported by three advantages namely, the primacy of human resources, product benefits, services, and excellence of infrastructure. The Mayor of the town of Mojokerto hoping to have a typical and excellent products, one of them is batik. Batik of Mojokerto is a craft culture which developed historically with the heyday of the Majapahit Kingdom. The uniqueness of the Mojokerto batik is in names of the pattern that less familiar to most people, such gedeg rubuh, matahari, mrico bolong, pring sedapur, grinsing, or surya majapahit. Attempts to introduce batik of Mojokerto certainly needed a medium that suits with the purpose. Promotion media is one of the purposes of introducing batik of Mojokerto to the wider community to international tourists.